Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan PT Aneka Tambang dan PT PErtamina Periode 2021-2024 - Khoirul Budi Cahyono; Haifah Haifah; Ahmad Sauqi (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to evaluate and compare the financial results of PT Aneka Tambang Tbk and PT Pertamina from 2021 to 2024 using financial ratio analysis. The ratios used include liquidity ratios such as the Current Ratio, Quick Ratio, and Cash Ratio; solvency ratios such as the Debt to Asset Ratio and Debt to Equity Ratio; activity ratios such as Working Capital Turnover, Fixed Assets Turnover, and Total Assets Turnover; and profitability ratios such as Net Profit Margin, Return on Assets, and Return on Equity. The research method used is quantitative research with a descriptive approach. The data used are secondary data obtained from the annual financial reports of PT Aneka Tambang Tbk and PT Pertamina for the period 2021 to 2024. Data analysis techniques are carried out by calculating financial ratios, comparing them with industry standards, and conducting cross-sectoral analysis to determine differences in the financial performance of the two companies. The results show that PT Aneka Tambang Tbk performed better in terms of liquidity and profitability, while PT Pertamina excelled in terms of activity and sales capacity, supported by its larger operational size. In terms of debt repayment capacity, both companies have different levels of debt in accordance with the characteristics of their respective industries. Overall, the financial performance of PT Aneka Tambang Tbk and PT Pertamina from 2021 to 2024 is considered satisfactory, although several ratios still fall short of industry standards and require further improvement in financial management efficiency.